If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4X + 17 + 28 = 6X Reorder the terms: 17 + 28 + 4X = 6X Combine like terms: 17 + 28 = 45 45 + 4X = 6X Solving 45 + 4X = 6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6X' to each side of the equation. 45 + 4X + -6X = 6X + -6X Combine like terms: 4X + -6X = -2X 45 + -2X = 6X + -6X Combine like terms: 6X + -6X = 0 45 + -2X = 0 Add '-45' to each side of the equation. 45 + -45 + -2X = 0 + -45 Combine like terms: 45 + -45 = 0 0 + -2X = 0 + -45 -2X = 0 + -45 Combine like terms: 0 + -45 = -45 -2X = -45 Divide each side by '-2'. X = 22.5 Simplifying X = 22.5
| 5/9=b-1/3 | | 1+5p=11+3p | | -56+3x=5x+80 | | 4(7y-6)-(9y+9)= | | 8(12+9)= | | 6m+2=8 | | a+(-11)=-13 | | 7x+10=210 | | 1+6k+8=-6k+9 | | 6(y-5)-4=20 | | -5x-17=-x-1 | | -8y^2+-5y^2+7y^2+-7y^2= | | (5^-2)x^-1/x^4(y^2) | | n/4-7=5 | | 2x+x(2x+30)=180 | | 4b+10= | | 10÷1/4 | | 7x^5-3x^2+4x-15=0 | | x-20=(20=x/3) | | 3x-8(-6)=-2 | | 5y=4x-30 | | -7c+8=8-7c | | -159+2x=51-12x | | -2(y-8)=-9y+37 | | 4.5-x=17 | | 11x-82=3x+126 | | 5+5d=37 | | 2(z+4)+8=4 | | 1/5=37/X | | 5(-4e+4)+7= | | 3x+4+2=39 | | 3(5+z)+2=10 |